A training program to enhance recognition of depression in nursing homes, assisted living, and other long-term care settings: Description and evaluation. Issue 3 (3rd July 2017) - Abrams, Robert C.; Nathanson, Mark; Silver, Stephanie; Ramirez, Mildred; Toner, John A.; Teresi, Jeanne A.
ABSTRACT: Low levels of symptom recognition by staff have been "gateway" barriers to the management of depression in long-term care. The study aims were to refine a depression training program for front-line staff in long-term care and provide evaluative knowledge outcome data. Three primary training modules provide an overview of depression symptoms; a review of causes and situational and environmental contributing factors; and communication strategies, medications, and clinical treatment strategies. McNemar's chi-square tests and paired t -tests were used to examine change in knowledge. Data were analyzed for up to 143 staff members, the majority from nursing. Significant changes ( p  < .001) in knowledge were observed for all modules, with an average change of between 2 and 3 points. Evidence was provided that participants acquired desired information in the recognition, detection, and differential diagnosis and treatment strategies for those persons at significant risk for a depressive disorder.